CASHLESS PAYMENT HESITANCY AMONGST UNIVERSITY STUDENTS - Noor Zahirah Mohd Sidek; Azyyati Anuar; Muhammad Hanif Othman; Ahmad Afif Ahmarofi, (JOURNAL INFORMATION AND TECHNOLOGY MANAGEMENT (JISTM), 2024)
Electronic payments, also known as cashless transactions, offer numerous advantages over traditional cash transactions, such as eliminating the need for change, reducing the risk of theft, and enhancing convenience. Many retailers have embraced electronic payment methods, including QR pay, credit or debit cards, and e-wallets, as viable alternatives for customers. Despite the availability of these options, there remains a reluctance among university students and staff to fully adopt cashless payment methods. In addition, issues such as concerns over privacy and data security, a lack of trust in the reliability of digital payment platforms, and inadequate awareness of how these systems function contribute to this hesitation. Thus, this study aims to explore the underlying reasons for this hesitation. Findings reveal that attitudes, knowledge levels, and willingness to embrace cashless transactions are key factors influencing this hesitancy. Accordingly, it is crucial for university administrations to implement appropriate digital policies to facilitate the transition towards a fully cashless and digitally integrated campus environment.